The Effectiveness of Using Youtube Videos as Learning Media in English Vocabulary Mastery - Sundanis, Rani Oktaviani; Jamiluddin; Eisenring, Moh.Abraham Akbar; Anggreni , Afrillia (LPPM Universitas Advent Indonesia, 2025)
This study aims to investigate the effectiveness of using YouTube videos as a learning medium to enhance English vocabulary mastery among second-grade students at SMA Negeri 3 Palu. The research was conducted using a quantitative approach with a pre-experimental design, involving one group that received treatment without a control group. The data were collected through a pre-test and post-test, each consisting of 20 multiple-choice questions focused on verbs and adjectives. The results showed a significant improvement in students’ vocabulary mastery after the implementation of YouTube videos in the learning process. The average score increased from 62.3 in the pre-test to 78.9 in the post-test, with a gain of 16.6 points. The Wilcoxon Signed-Rank Test was used to analyze the data, as the same group was tested twice and the data did not meet normality assumptions. The test yielded a statistical value of 0.0 with a p-value of 0.007 (p < 0.05), indicating a significant difference between the pre-test and post-test scores. Based on these findings, the null hypothesis was rejected, and the alternative hypothesis was accepted, confirming that the use of YouTube videos is effective in improving students’ English vocabulary mastery. This study suggests that English teachers consider integrating YouTube videos into classroom instruction to foster a more engaging and effective learning environment.